2020
DOI: 10.1038/s41598-020-72053-z
|View full text |Cite
|
Sign up to set email alerts
|

Attosecond betatron radiation pulse train

Abstract: High-intensity X-ray sources are essential diagnostic tools for science, technology and medicine. Such X-ray sources can be produced in laser-plasma accelerators, where electrons emit short-wavelength radiation due to their betatron oscillations in the plasma wake of a laser pulse. Contemporary available betatron radiation X-ray sources can deliver a collimated X-ray pulse of duration on the order of several femtoseconds from a source size of the order of several micrometres. In this paper we demonstrate, thro… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 53 publications
(67 reference statements)
0
3
0
Order By: Relevance
“…This was expected, as in the neighbors of the node of the longitudinal gradient, the scalar potential is symmetric, which leads to similar trapping positions for particles extracted at phases ξ e and −ξ e , provided that |ξ e | 1. We evaluate the terms of Equation (10) for the reference case given by the ReMPI simulations we run and for the case of the fully evacuated bubble. For the blowout case, we will use the analytical results from [23] and we will assume that both a background plasma and an ionization pulse with the same parameters as the ReMPI PIC simulations will be employed.…”
Section: Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…This was expected, as in the neighbors of the node of the longitudinal gradient, the scalar potential is symmetric, which leads to similar trapping positions for particles extracted at phases ξ e and −ξ e , provided that |ξ e | 1. We evaluate the terms of Equation (10) for the reference case given by the ReMPI simulations we run and for the case of the fully evacuated bubble. For the blowout case, we will use the analytical results from [23] and we will assume that both a background plasma and an ionization pulse with the same parameters as the ReMPI PIC simulations will be employed.…”
Section: Parametermentioning
confidence: 99%
“…The generation of relativistic electron bunches with durations in the attosecond range can lead to pump/probe beams, which can be fruitfully employed to unveil ultrafast dynamics [1]. In the context of plasma wakefield acceleration either driven by laser pulses (LWFA) [2] or particle beams (PWFA) [3], several methods have been proposed to specifically generate electron beams with a duration below the femtosecond scale, from the pioneering work about beam compression of beams externally injected ahead of the driver laser pulse [4][5][6], dense attosecond beams with up-ramp density transitions [7], attosecond beams via density modulations [8], attosecond trains obtained by betatron quivering modulations [9,10], few-cycle TW pulses-driven electron beams [11,12], attosecond trains via ionization injection [13] and high-brightness electron beams through ionization injection in hybrid LWFA/PWFA schemes [14,15]. As the disentanglement of the electron beam parameters including length, charge, average energy, energy spread and emittance are of paramount importance for the feasibility of the pump/probe attosecond source, thus a flexible injection/acceleration scheme should be preferred.…”
Section: Introductionmentioning
confidence: 99%
“…Besides betatron radiation [18][19][20][21] emitted by transversely oscillating electrons during their acceleration process, the interaction of such energetic electron bunches with high-Z converters results in the emission of intense broadband X-ray radiation through a process of Bremsstrahlung [22][23][24][25][26] . The idea to convert the LWFA accelerated electron into hard X-rays by their stopping in a high-Z converter is highly topical and intensively investigated nowadays.…”
Section: Introductionmentioning
confidence: 99%
“…Previous numerical simulations have shown that a high-brightness, high-energy attosecond γ-ray source can be generated via a laser pulse colliding head-on with a counter-propagating electron beam [27][28][29][30]. In recent years, different target geometries, including flat target [31], gas target [32,33], wire target [34], channel target [35] and cone target [36] have been proposed, to enhance the quality of attosecond x/γ-ray pulses. As an example, a laser-driven flying plasma layer is proposed for ultra-brilliant femtosecond γ-ray pulse emission [37].…”
Section: Introductionmentioning
confidence: 99%
“…As schematically shown in figure 1, the first laser (drive laser, DL) illuminates a nanofoil, producing a single RES with high charge and high energy at stage I; the second counter-propagating laser (scattering laser, SL) collides with the RES, generating an isolated subfemtosecond γ-ray pulse via NCS at stage II. Compared with the scheme by laser irradiating a gas target as mentioned above [32], our scheme achieves a single RES with a charge of more than 6 nC, a cutoff energy of 345 MeV and a duration of 800 as. In addition, we explore the polarization degree of the generated γ-ray pulse by using a proof-of-principle calculation.…”
Section: Introductionmentioning
confidence: 99%